2023
DOI: 10.1007/s00262-022-03360-9
|View full text |Cite|
|
Sign up to set email alerts
|

Determinants of activity and efficacy of anti-PD1/PD-L1 therapy in patients with advanced solid tumors recruited in a clinical trials unit: a longitudinal prospective biomarker-based study

Abstract: Immune-checkpoint inhibitors (ICI) have revolutionized the therapeutic landscape of cancer. However, optimal patient selection is still an unmet need. One-hundred-forty-six patients with metastatic cancer candidates to ICI at the Hospital Clinic of Barcelona Clinical Trials Unit were prospectively recruited in this observational study. Blood samples were collected at different timepoints, baseline LIPI score calculated and pre-ICI archived tissues retrieved to evaluate PD-L1, tumor-infiltrating lymphocytes (TI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Therefore, patients that did not undergo surgery were excluded from this study. Our study has potential implications with respect to the efficacy of CPI in patients with brain metastases that may be candidates to receive CPIs after brain metastasis resection and RTx [20][21][22][23] . In this regard in patients with metastatic disease several retrospective studies indicated that timing of initiation of corticosteroids may influence therapy response to CPI; for example, Maslov and colleagues showed that patients treated with corticosteroids within 2 months of initiation with CPI showed significantly shorter OS than patients receiving corticosteroids after 2 months of initiation of treatment with CPIs 22 .…”
Section: Discussion/conclusionmentioning
confidence: 97%
“…Therefore, patients that did not undergo surgery were excluded from this study. Our study has potential implications with respect to the efficacy of CPI in patients with brain metastases that may be candidates to receive CPIs after brain metastasis resection and RTx [20][21][22][23] . In this regard in patients with metastatic disease several retrospective studies indicated that timing of initiation of corticosteroids may influence therapy response to CPI; for example, Maslov and colleagues showed that patients treated with corticosteroids within 2 months of initiation with CPI showed significantly shorter OS than patients receiving corticosteroids after 2 months of initiation of treatment with CPIs 22 .…”
Section: Discussion/conclusionmentioning
confidence: 97%
“…Finally, PD-L1 is now used as a major predictive biomarker of response to ICI 9 . Here we aimed at evaluating its association with genomic alterations in solid tumors to speculate on a potential role beyond immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor mutational burden (TMB) is usually de ned as the number of somatic mutations per megabase (Mb) of interrogated genomic sequence and is a potential biomarker of response to ICI 9 . The Oncofocus assay covers ~ 1.2 Mb over 505 genes, complying with the evidence-based suggestion that gene panels of at least 1 Mb are needed for TMB measurement [16][17][18] .…”
Section: Immunohistochemistry For Pd-l1 Expression and Tumor Mutation...mentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the immune system in controlling cancer development, treatment responses and long-term survival of cancer patients by manipulating immune response with several therapeutic immunotherapeutic strategies has already been established or under intensive investigation (13)(14)(15); consequently, numerous researchers have directed their efforts toward investigating immune-related genes in the pursuit of developing reliable predictive models for immunotherapy outcomes and patients prognosis. On this Research Topic of Tian et al, Yang et al and Liu et al developed prognostic models based on different immunerelated genes, which seem to be promising in effectively assist clinicians with medical diagnoses, evaluating patient prognosis and formulating diverse treatment strategies.…”
Section: Diagnostic and Prognostic Biomarkersmentioning
confidence: 99%